Pelatihan Dasar Microsoft Word dan Format Penulisan Ilmiah untuk Mahasiswa Baru Pesma Universitas Muhammadiyah Bengkulu - Anderson, Josefin; Ulandara, Elka Putra; Saputra, Gunawan; Arifin, Ilham; Pratama, Erick Putra; Fitriah, Fitriah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Basic training on Microsoft Word and scientific writing was held at Pesma Putra Universitas Muhammadiyah Bengkulu to improve the digital literacy of new students. This activity was based on the participants' lack of understanding of important features in Microsoft Word that support academic writing, such as headings, automatic table of contents creation, page numbering, and citation management. The implementation method adopted a hands-on approach (learning by doing) with material delivery, practical sessions, and evaluation through a Google Form-based pre-test and post-test. The assessment results showed a significant increase in participants' understanding. The average pre-test score showed low understanding, while the post-test score rose to the category of understanding and very understanding according to the Likert scale. In addition to the increase in numbers, participants also displayed high enthusiasm during the practice. This activity shows that short training using interactive methods can have a positive influence on students' basic skills in using word processing software for academic purposes. This service activity is expected to be a reference for implementing similar training in the future, as well as supporting the improvement of digital literacy in the campus environment, especially in welcoming new students.